Success Factors in Triple Helix Coordination: Small-Medium Sized Enterprises in Western Java - Somariah Fitriani; Sintha Wahjusaputri; Ahmad Diponegoro (ETIKONOMI, 2019)
Triple helix model is a model of a knowledge-based economy, which collaborates with the university, business, and government sectors to help small and medium enterprises (SMEs) boost their business. The issue is the three actors have not yet synergized optimally in the development of SMEs. Hence, this study was to identify the critical success factors of the triple helix model for SMEs. This study employed a meta-ethnography and factor analysis to obtain components and indicators of the success factors. The result showed that 37 items of critical success factors have good content validity and excellent homogeneity reliability. Based on these success factors, a triple helix model consisting of six stages has developed. It indicates that these critical success factors make an essential contribution to the development and success of SMEs to achieve the goal of the program.JEL Classification: L52, L53